KESIAPSIAGAAN MASYARAKAT TERHADAP MEGATHRUST DI KELURAHAN SIDOHARJO DAN DESA SEDENG KECAMATAN PACITAN KABUPATEN PACITAN - Lulut Yuliana Mardiani; Ahmad; Setya Nugraha (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2023)
This research was carried out in Sidoharjo Village and Sedeng Village, Pacitan District, Pacitan Regency with the aim of knowing the community's preparedness for megatrhusts in Sidoharjo Village and Sedeng Village, Pacitan District, Pacitan Regency. The research method used in this research is descriptive qualitative with a spatial approach. The research was conducted on community leaders in Sidoharjo Village and Sedeng Village with research samples using regional samples based on topography and knowledge. Data collection techniques in this research are observation and interviews. Then, to test the validity using data triangulation techniques. The results of the research show the level of community preparedness in facing megatrusts in Sidoharjo Village and Sedeng Village, Pacitan District are included in the same classification, that both areas have individual community preparedness that is very ready to face megatrust disasters.